Analysis of Factors Influencing Knowledge Sharing with the Moderating Effect of Perceived Organizational Support Among Civil Servants in Indonesia: Case Study of BPS-Statistics Indonesia - Muhammad Rizki; Dana Indra Sensuse; Sofian Lusa; Nadya Safitri; Damayanti Elisabeth (Dinasti Research, 2026)
As an essential component of knowledge management within organizations, knowledge sharing helps to improve teamwork, especially in government institutions that involve civil servants. This research aims to determine the factors that influence Knowledge Sharing Behavior (KSB), performing consideration of Knowledge Sharing Intention (KSI) as an endogenous driver, Perceived Organizational Support (POS) as a moderating variable, and self-efficacy, subjective norm, horizontal trust, vertical trust, IT adoption, and public service motivation as exogenous variables. Based on a survey of 327 respondents at the BPS-Statistics of Indonesia, the results reveal that Self-efficacy, Subjective Norms, and IT Adoption concurrently have a positive direct impact on both Knowledge Sharing Intention and Knowledge Sharing Behavior. Furthermore, Public Service Motivation and Knowledge Sharing Intention also exhibit a positive direct effect on the target variable. Nevertheless, neither horizontal nor vertical trust has an impact on the way people share knowledge. Meanwhile, regarding the moderating effects, perceived organizational support possesses the power to specifically strengthen the relationship between Self-efficacy and Knowledge Sharing Intention, whereas its interaction effects on other behavioral pathways are found to be non-significant.